Spontaneous renal artery dissection: angioplasty with stent implantation in one-year follow-up - Souza,Katia Pinheiro de (2022)
ABSTRACT Spontaneous renal artery dissection is an unusual and idiopathic condition in most cases. In young, mildly symptomatic patients, diagnosis may be difficult, frequently culminating in delay in treatment. This report presents the case of a 40-year-old male patient, with severe hypertension of sudden onset, and difficult management of oral medication. In etiological investigation, Echo-Doppler of renal arteries showed signs of hemodynamically relevant right renal artery stenosis. Arteriography showed presence of double-lumen and thrombus in the vessel lumen, indicating dissection. The proposed treatment was endovascular approach after failure of isolated medical treatment, option which included the aspiration of the thrombus by Penumbra System® device and balloon angioplasty, followed by right renal artery stenting. Improvement of immediate sonographic control of peak systolic velocity and renal-aortic ratio was shown, with a consequent reduction of systemic arterial blood pressure and stabilization of renal function. Within the following year, the patient presented in-stent stenosis and was successfully treated with balloon angioplasty.